How Journalists and Social Media Users Perceive Online Fact-Checking and Verification Services. (21st October 2018) - Brandtzaeg, Petter Bae; Følstad, Asbjørn; Chaparro Domínguez, María Ángeles
Abstract : While services for fact-checking and verification to counter fake news in social media have increased, little research has investigated how journalists and the public perceive such services. This study reflects the outcomes of REVEAL, a three-year European Union research project investigating the use and impact of services for fact-checking and verification. Based on interviews with 32 young journalists and content analysis of social media users' online conversations, we contribute new knowledge about the ways that journalists and social media users perceive online fact-checking and verification services. The findings suggest that, while young journalists were largely unfamiliar with or ambivalent about such services, they judged them as potentially useful in the investigative journalistic process. Yet, they were unwilling to rely exclusively on these tools for fact-checking and verification. A comparison of journalists' perceptions with those of social media users reveals social media users are similarly ambivalent. Some accentuated the usefulness of such services, while others expressed strong distrust. However, the journalists displayed a more nuanced perspective, both seeing these services as potentially useful and being reluctant to blindly trust a single service. Design strategies to make online fact-checking and verification services more useful and trustworthy are suggested.